New Development Assistance
XX, 203 p.
Keywords: This book explores the changing face of development assistance. China's One Belt, One Road development program is the largest international investment scheme in history, surpassing the Marshall Plan by an order of magnitude. In 2017, a group of top scholars from Fudan, the London School of Economics, and other institutions like the Institute of Development Studies, Australian National University, and World Bank gathered to share findings and ideas about the nature of New Development Assistance. A compilation of their findings, this book will be of interest to NGOs, policymakers, and academics. Yijia Jing is a Changjiang Scholar, Seaker Chan Chair Professor of Public Management, and Director of the Institute for Global Public Policy of Fudan University. He is editor-in-chief of Fudan Public Administration Review and co-editor of International Public Management Journal. Alvaro Mendez is co-director of the Global South Unit and a Senior Research Fellow at the London School of Economics. His most recent publications include: Global Governance in Foreign Policy (Oxford University Press, 2018); and The China-Latin America Axis: Emerging Markets and their Role in an Increasingly Globalised World (Palgrave, 2018). Yu Zheng is a Professor at the School of International Relations and Public Affairs, Fudan University. He is the author of Governance and Foreign Investment in China, India, and Taiwan: Credibility, Flexibility, and International Business (University of Michigan Press). .